Interfacial Bonding Characteristic And Fluid Transport Properties Between Normal Concrete Substrate And Green Ultra-High Performance Fiber Reinforced Cementitious Composites - Hassan, Mohd Helmi (2016)
Rehabilitation of concrete structure has been widely used and upgraded nowadays as the existing structures exposed to the severe mechanical loading and environment. Based on the concerns stated, the method and procedure of rehabilitation works are taking into consideration in order to produce an effective way to strengthen the properties of existing structure. The application of ultra-high performance fiber reinforced cementitious composites (UHPFRCC) as rehabilition or repair material nowaday show an excellent feedback as it is high in mechanical and durability properties. However, this product is considered as uneconomical and less environmental-friendly as the requirement of total volume of cement is high in order to achieve the ultra-high mechanical strength. As a solution, a patented green UHPFRCC, which has been known as green Universiti Sains Malaysia Reinforced Concrete (GUSMRC) was developed. This concrete is classified as eco-friendly construction material as it replaced 50 % of cement total volume by pozzolanic material, ultra-fine POFA (UPOFA). As the objectives of this study were to investigate the interfacial bonding and fluid transport properties between the old concrete and newly repair material, GUSMRC was applied as the new repair material with two different types of surface treatment/roughness; sand blasting and grinding, where as the normal concrete substrate acted as an old concrete. Interfacial bond strength characteristic were evaluated between these two surface textures. In addition, the fluid transport properties of repair material was also assessed on the monolithic samples and the composite samples (repair material). For composite samples, two types of layering condition were applied; overlay and half-half condition. The final results showed that GUSMRC was successfully accepted as a repair material to reduce the fluid transport values of old concrete. The bonding properties were also successfully accepted with an excellent quality of bond strength. The sand blasting surface treatment led all the bonding properties results; the roughest and more effective surface treatment compared to grinding.